2020
DOI: 10.1029/2019gl085652
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Evolution of Canopy Stomatal Conductance for a Prairie and Maize Field in the Midwestern United States from Continuous Carbonyl Sulfide Fluxes

Abstract: There are inherent challenges in scaling stomatal conductance (g s) from leaf to canopy particularly over seasonal time scales when species distribution and canopy structure evolve. We address this gap using carbonyl sulfide (OCS) and CO 2 fluxes from a predominantly C3 prairie and C4 maize field in the midwestern United States. The g s derived from OCS fluxes captured a transition in the stomatal limitation on gross primary productivity (GPP) through the growing season as well as seasonally persistent g s dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 81 publications
5
36
0
Order By: Relevance
“…Assimilation of HIPPO observations slightly improves this model bias, which implies that additional observations are urgently required to constrain sources and sinks of COS. We finally find that the biosphere flux dependency on the surface COS mole fraction (which was not accounted for in this study) may substantially lower the fluxes of the SiB4 biosphere model over strong-uptake regions. Using COS mole fractions from our inversion, the prior biosphere flux reduces from 1053 to 851 Gg a −1 , which is closer to 738 Gg a −1 as was found by Berry et al (2013). In planned further studies we will implement this biosphere dependency and additionally assimilate satellite data with the aim of better separating the role of the oceans and the biosphere in the global COS budget.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…Assimilation of HIPPO observations slightly improves this model bias, which implies that additional observations are urgently required to constrain sources and sinks of COS. We finally find that the biosphere flux dependency on the surface COS mole fraction (which was not accounted for in this study) may substantially lower the fluxes of the SiB4 biosphere model over strong-uptake regions. Using COS mole fractions from our inversion, the prior biosphere flux reduces from 1053 to 851 Gg a −1 , which is closer to 738 Gg a −1 as was found by Berry et al (2013). In planned further studies we will implement this biosphere dependency and additionally assimilate satellite data with the aim of better separating the role of the oceans and the biosphere in the global COS budget.…”
supporting
confidence: 64%
“…Zumkehr et al (2018) recently presented a new global anthropogenic emission inventory for COS. The new anthropogenic emission estimates are, with 406 Gg a −1 (as S equivalents) 1 in 2012, substantially larger than the previous estimate of 180.5 Gg a −1 by Berry et al (2013). Another recent study (Stinecipher et al, 2019) concluded that it is unlikely that biomass burning accounts for the balance between sources and sinks of COS, due to the relatively small contribution of biomass burning to the total emissions ((60 ± 37) Gg a −1 ).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations